The Influence of Self Instruction Techniques on Students’ Learning Burnout at State Madrasah Aliyah - Lilis Sartika; Fauziah Nasution (Universitas Muhammadiyah Enrekang, 2024)
This research was conducted to determine the influence provided by group counseling services using Self Instruction to minimize the level of learning boredom of XI MIPA 3 students at MAN 3 Medan. This research method uses an experiment with a one group pretest-posttest design. Where there were 32 students as the population and a sample of 7 students who had high learning boredom scores was taken using the purposive sampling technique. The data analysis techniques used are the Normality Test and the T Test (paired sample test). With the help of the SPSS Version 22.0 For Windows analysis tool. Based on the research results before and after the treatment, the Sig value was obtained. (2-tailed) is 0.000, then < 0.05 H0 is rejected and Ha is accepted. The results of this study showed that there was a decrease in the level of student learning boredom after being given group counseling services using the Self Instruction technique as treatment for students at Madrasah Aliyah Negeri 3 Medan.